Intervensi Relaksasi Otot Progresif (Progressive Muscle Relaxation) pada Pasien Kanker yang Mengalami Fatigue - Dwi Suryani; Tuti Nuraini; Dewi Gayatri (Journal of Telenursing (JOTING), 2022)
This study aims to determine the effect of progressive muscle relaxation (PMR) on fatigue in cancer patients. The method used is a systematic review. The results showed that of the 7 articles reviewed, 6 showed that PMR could reduce fatigue or fatigue in cancer patients and 1 article showed no significant difference in applying progressive muscle relaxation to fatigue or fatigue. In conclusion, PMR can reduce the fatigue experienced by cancer patients. Keywords: Cancer, Fatigue, Progressive Muscle Relaxation